Perceptions of Experience and Tourist Loyalty Towards the Attractions of Sawah Lukis Binjai: A Phenomenological Study From A Destination Marketing Perspective - Widya Octovia Rini Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore in depth how tourists interpret their experiences when visiting Sawah Lukis Binjai and how these experiences contribute to the formation of loyalty to the destination. Using a phenomenological approach, the study relies on personal narratives obtained through in-depth interviews and participant observation to reveal a more authentic understanding of the tourism experience. The results show that Sawah Lukis is not merely viewed as an ordinary tourist attraction, but as a space capable of evoking emotional attachment, cultural appreciation, and spiritual reflection for visitors. The visual beauty, interactive activities, the tranquil rural atmosphere, and warm social interactions contribute significantly to shaping the destination's positive image. Authentic and personally meaningful experiences encourage tourists' desire to revisit and foster an intrinsic drive to recommend the destination to others. Thus, tourism experiences are a crucial element in designing sustainable and value-oriented destination marketing strategies.